VideoHound's golden movie retriever [2007] - Craddock, Jim (Gale virtual reference library, 2006)
Reviews movies that are available on DVD or tape. Each entry includes title, alternate title, one-to four-bone rating, year released, MPAA rating, brief review, length, format, country of origin, cast, technical personnel, awards and made-for-television/cable/video designations.